Research trends of Islamic Communication and Broadcasting (KPI) students and challenges of Islamic communication science - Usman Usman; Abdul Manan; Yummil Hasan (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2022)
The scientific development of Islamic communication is determined by research based on Islamic values. However, the challenge is that Islamic communication deals with established general communication sciences. This study aims to see trends in the research direction of Islamic Communication and Broadcasting Study Program students and its position in the development of Islamic communication science. This study uses a type of qualitative study conducted at the Department of Islamic Communication and Broadcasting, Faculty of Da'wah and Communication Studies, UIN Imam Bonjol Padang with documentation data collection techniques. The objects studied were original documents resulting from student research for the last 5 (five) years totaling 298 titles. The study findings show that 40.98% of students choose mass communication and new media studies, only 19.67% choose da'wah communication studies and da'wah scholarship. This certainly has an influence on the scientific construct of Islamic communication. This means that the discourse on communication science is still dominated by